LEVIN-RICHARDSON, S. The brothel of Pompeii. Sex, Class and Gender at the Margins of Roman Society. Cambridge; Nova Iorque: Cambridge University Press, 2019. 266p. - Barbosa Junior, Jorge Steimback (Revista Diálogos Mediterrânicos, 2020)
LEVIN-RICHARDSON, S. The brothel of Pompeii. Sex, Class and Gender at the Margins of Roman Society. Cambridge; Nova Iorque: Cambridge University Press, 2019. 266p.